Aspects of bull reproduction with emphasis on cattle in Ethiopia. II. Sperm production capacity and semen characteristics - Tegegne, Azage; Kassa, T.; Mukasa-Mugerwa, E. (Ethiopian Society of Animal Production, 1995)
The efficiency of cattle breeding and production depends to a large extent on the reproductive performance of the herd, with the bull playing a major role. Large differences in fertilizing ability between bulls exists, and such differences are due to the characteristics of individual bulls rather than to factors such as age, bull to cow ratio or type of mating. In Ethiopia, cattle breeding is mostly uncontrolled, making genetic improvement difficult. If improvement in cattle production is envisaged in the coming years, appropriate bulls election criteria have to be established and applied and controlled and selective breeding of cow herds should be implemented. This paper examines available information on bull reproduction in Ethiopia and highlights the different physiological functions of the bull in relation to reproductive performance. Major factors which influence bull reproductive function and fertility are discussed. Comparative data from other Bos indicus and Bos taurus breeds of cattle are included and areas of future research are outlined.